AN ANALYSIS OF TEACHER’S DISCOURSE MARKERS IN THE CLASSROOM INTERACTION - Nazifah Rahma Sukriyah; Jismulatif Jismulatif; Syofia Delfi (Tell-us Journal)
This research aims to find out the types of discourse markers used in the teacher talk and the reasons for the presence of its dominant use. The subject of this study was an English teacher of SMP YLPI Marpoyan. This study used a descriptive qualitative design. The data was gathered through observation, recording, and interview. The data were evaluated using Fung and Carter's (2007) hypothesis. The result of the study revealed that there were four types of teacher discourse markers in English classroom interaction: interpersonal, referential, structural, and cognitive. Interpersonal marker is the most dominant type of discourse markers used by the teacher with 49,21%, referential 23,43%, structural 21,87%, and cognitive 5,46%. The reasons for the teacher's use of interpersonal markers as the dominant one were influenced by the presage category and the context category. The English teacher was suggested to understand the importance of employing discourse markers in conversations to add to the efficacy of the teaching and learning process.